Naturalistic examination of the anxiolytic effects of medical cannabis and associated gender and age differences in a Canadian cohort - Meenu Minhas; Stephanie E. Lunn (BMC, 2023)
Abstract Background The aim of the current study was to examine patterns of medical cannabis use in those using it to treat anxiety and to investigate if the anxiolytic effects of cannabis were impacted by gender and/or age. Methods Patient-reported data (n = 184 participants, 61% female, 34.7 ± 8.0 years) was collected through the Strainprint® app. Tracked sessions were included if the method of administration was inhalation, treatment was for anxiety and the product used was dried flower. The final analyzed dataset encompassed three of the most commonly utilized dried flower products in anxiety sessions. Independent sample t-tests were used. The core analysis examined within subject changes overtime (pre-medication to post-medication) and interactions between time with two candidate moderators [gender (male, female) and age (18-29, 30-39, and 40 + years old)] by using analysis of variance (ANOVA). For significant main effects of interactions, post hoc tests were conducted using a Bonferroni correction. A secondary analysis examined differences in proportion of emotives endorsed as a function of gender or age using chi-square test of independence. Results Cannabis consumption resulted in a significant decrease in anxiety scores among both males and females (average efficacy of 50%) and efficacy was similar across the three cultivars. However, gender differences in efficacy were identified in two of the cultivars. All age groups experienced significant reductions in their anxiety post cannabis consumption; however, the 40 + year old group had significantly less efficacy than the other groups. The overall optimal dosing for the entire cohort was 9-11 inhalations for males and 5-7 inhalations for females, with some variation in dosing across the different cultivars, genders and age groups. Conclusions We found all three cultivars had significant anxiolytic effects and were well-tolerated. Some limitations of the study are the moderate sample size, self-reported diagnosis of anxiety, unknown comorbidities and experience with cannabis, whether other drugs or cannabis products were used, and restriction to solely inhaled administration. We suggest that the gender and age differences in optimal dosing could support both healthcare practitioners and patients initiate medical cannabis treatment for anxiety.